2018
DOI: 10.1186/s13048-018-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

Innovative multi-protectoral approach increases survival rate after vitrification of ovarian tissue and isolated follicles with improved results in comparison with conventional method

Abstract: BackgroundIn recent years, autotransplantation of cryopreserved ovarian tissue became a promising approach to preserve female fertility. The slow freezing is the most effective technique which resulted in greater live birth incidence so far. Despite that, interest to vitrification of the ovarian tissue is swiftly growing, thereby undermining the necessity for further improvements in the technique. In present study, we evaluated possibilities to increase follicle survival rates adopting innovative multi-protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In contrast, other studies concluded that slow cooling was superior to vitrification. [69][70][71][72][73] Still other data indicated both techniques to be similar in terms of the percentage of morphologically normal follicles and apoptotic cells. 74,75 Shi et al 76 recently conducted a metaanalysis that included 14 studies evaluating the efficacy of vitrification vs slow cooling of ovarian tissue.…”
Section: Fertility Preservation In Prepubertal Femalesmentioning
confidence: 85%
“…In contrast, other studies concluded that slow cooling was superior to vitrification. [69][70][71][72][73] Still other data indicated both techniques to be similar in terms of the percentage of morphologically normal follicles and apoptotic cells. 74,75 Shi et al 76 recently conducted a metaanalysis that included 14 studies evaluating the efficacy of vitrification vs slow cooling of ovarian tissue.…”
Section: Fertility Preservation In Prepubertal Femalesmentioning
confidence: 85%
“…44 Partially, our handling approach ressembles the protocol of Nikiforov, using unlinked metal meshes for carrying ovarian tissue samples with 0.28 mm wire diameter and mesh aperture of 1.31 mm for vitri cation and insertion into cryovials after vitri cation. 45 Our approach included metal meshes with wire diameters of 0.25 mm and opening sizes of 0.38 mm. This ensures a large contact area of the cortex tissue on a metal carrier thin as possible, potentially in uencing on the thermal conductivity while the meshes were pre linked with the caps of the cryovials.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, eCG was used as an alternative FSH hormone for superovulation induction by improving the process of follicle recruitment in several mammal models [68]. Indeed, it was successfully used in small mammals, such as mice rats [69] rats alone [70], medium-large sized mammals such as sheep [71][72][73], goats [74], cows [75], mares [76], and pigs [77].…”
Section: Discussionmentioning
confidence: 99%